The Effect Of Shopping Orientation, Online Trust, And Purchase Experience On Interest To Buy Online - Afifah Indah Putri; Yulius Wahyu Setiadi (Universitas Mercu Buana, 2022)
The Effect of Online Trust Shopping Orientation andPurchase Experience on Online Purchase Intention.This study aimed to find out the effect of shopping orientation, online trust, and purchase experience on online purchase intention.The sample in this study were Shopee online shop consumers in the city of Argamakmur, North Bengkulu Regency. The study method employed was a quantitative method with an associative approach. The results of this study indicate that: (1) There is a positive influence of the shopping orientation variable on online purchase intention. Based on the results of the partial test, the t-count is 3.304 and the regression coefficient is 0.118 with a significance of0.001; (2) There is a positive effect of online trust variable on online purchase intention. Based on the results of the partial test, the t-count is 6.615 and the regression coefficient is 0.554 with a significance of 0.000; (3) There is a positive effect of the Purchasing Experience variable on Online Purchase Intention. Based on the results of the partial test, the t-count is 3.129 and the regression coefficient is 0.217 with a significance of 0.002; and (4) Shopping orientation, online trust, and purchase experience have a positive effect on online purchase intention. This is proven by the test results gained by the calculated f value of 85,450, with a significance (0.000 < 0.050).